Patriarchal Structures in Islamic Law and Indonesian Positive Law: A Comparative Legal Analysis from a Gender Justice Perspective - Ramadhan, Rahmat Gilang; Hibatullah, Mohammad Rafii'; Farichudzaki, W.K.; Aji, Rajali H. (Department of Comparative Mazhab Comparative, Fakulty of Shariah and Law, 2025)
Abstract: This study critically examines the persistence of patriarchal bias in Indonesia’s legal system by comparing Islamic law and positive law through a gender justice lens. This research specifically identifies how patriarchal structures are embedded in family law norms, judicial reasoning, and institutional legal practices, particularly in matters of marriage, lineage, and gendered legal authority. Using a qualitative normative method with a comparative socio-legal approach, the study analyzes statutory regulations, classical and contemporary Islamic legal doctrines, and scholarly interpretations relevant to the Indonesian legal context. The findings reveal a fundamental divergence between the two systems: while positive law formally endorses gender equality, patriarchal bias persists at the level of legal interpretation and implementation, especially within judicial institutions; conversely, Islamic law, when interpreted textually, may reproduce gender hierarchy, yet offers a strong emancipatory potential when re-read through maqāṣid al-sharī‘ah and egalitarian legal reasoning. The study argues that patriarchal bias is not merely normative but institutional, and that meaningful legal reform requires not only doctrinal revision but also transformation of judicial reasoning and legal culture. Keywords: patriarchy, Islamic law, Indonesian positive law, judicial reasoning, gender justice Abstrak: Penelitian ini mengkaji tentang bias patriarki dalam sistem hukum Indonesia melalui analisis komparatif antara hukum Islam dan hukum positif dari perspektif keadilan gender. Studi ini secara spesifik mengidentifikasi bagaimana struktur patriarkal terinternalisasi dalam norma hukum keluarga, pola judicial reasoning, serta praktik kelembagaan peradilan, terutama dalam isu perkawinan, nasab, dan otoritas hukum berbasis gender. Dengan metode kualitatif normatif dan pendekatan komparatif sosio-legal, penelitian ini menelaah peraturan perundang-undangan, doktrin hukum Islam klasik dan kontemporer, serta pandangan akademik yang relevan dengan konteks Indonesia. Temuan penelitian menunjukkan perbedaan fundamental antara kedua sistem: hukum positif secara normatif menjamin kesetaraan gender, namun masih mereproduksi bias patriarki pada tingkat interpretasi dan implementasi hukum, khususnya dalam praktik peradilan; sementara itu, hukum Islam dalam pembacaan tekstual berpotensi melanggengkan hierarki gender, tetapi sekaligus menyediakan landasan emansipatoris yang kuat melalui pendekatan maqāṣid al-sharī‘ah dan penalaran hukum yang egaliter. Penelitian ini menegaskan bahwa bias patriarki bersifat institusional, bukan semata normatif, sehingga reformasi hukum yang berkeadilan gender mensyaratkan transformasi penafsiran hukum, penguatan nalar hakim, dan perubahan budaya hukum. Kata Kunci: patriarki, hukum Islam, hukum positif Indonesia, judicial reasoning, keadilan gender